Pengaruh Pemupukan Dan Pemangkasan Terhadap Pertumbuhan Dan Hasil Melon (Cucumis melo L.) di Lahan Kering: Effect of Fertilization and Pruning on Growth and Yield of Melon (Cucumis melo L.) in Dry Land - Jayaputra Jayaputra; Bambang Budi Santoso; Komang Damar Jaya (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2022)
The aim of this study was to determine the effect of a combination of NPK fertilizer and liquid organic fertilizer (POC) and pruning and its interaction on the growth and yield of melon plants on dry land. The experiment used a two-factor factorial randomized block design, namely: Application of NPK + Liquid Organic Fertilizer (POC) (b0 = 100% NPK without POC; b1 = 50% NPK + Bio-Extrem POC; b2 = 50% NPK + Organox POC) ; and Pruning (p0 = No Pruning, p1 = Pruning by maintaining 2 main branches). The results showed that pruning had a significant effect on the percentage of class C fruit quality, while fertilization treatment had no significant effect on all observed parameters. The interaction of the combination of fertilization and pruning had no significant effect on the growth and yield of melons, however, the combination of fertilizing with pruning was able to avoid fruit weight <1 kg (class C fruit quality). The use of a combination of 50% NPK + POC (Bioektrim / Organox) fertilizer and pruning can be used as a technology package in an effort to reduce the use of inorganic fertilizers and increase the yield and quality of melon fruit on dry land.